3 - Privately Sponsored Students and Other Income-Generating Activities at the University of Nairobi*: Crispus Kiamba - Crispus Kiamba, (Journal of Higher Education in Africa, 2004)
* An earlier version of this paper was presented to a conference, “Improving Tertiary Education in Sub-Saharan Africa: Things That Work!” sponsored by the Association of African Universities and the World Bank, in Accra, Ghana, September 23–25, 2003. Beginning in the 1994–1995 academic year, the government sharply cut university funds from the Kenyan exchequer, challenging the University of Nairobi to diver- sify its revenue sources. In response, the university adopted the concept of the “entrepreneurial university” and created a wholly owned, independent, profit-mak- ing holding company, the University of Nairobi Enterprises and Services Limited (UNESL). Those involved in the planning determined that the university should concentrate on its core competence, which was adding value to knowledge. The most fruitful—and radical—development was the addition of the Module II (or parallel) programs that accept privately sponsored students, thus embracing tuition fees and the concept of cost-sharing at least for these students but for the benefit of the entire university. Overcoming initial resistance, Model II and other income- generating activities have allowed the university to greatly enhance its financial base and increase access to its educational programs.